Outcomes of gallstone complications during the COVID pandemic. Issue 1 (31st December 2020) - Isherwood, J; Karki, B; Chung, W Y; AlSaoudi, T; Wolff, J; Malde, D; Bhardwaj, N; Garcea, G; Dennison, A R
Abstract : As data and metadata from the SARS-CoV-2 pandemic mature, the true impact on non-cancer, non-emergency surgical practice is becoming apparent. The authors present data on the impact of gallstone disease in their unit during 5 months of the COVID-19 pandemic (March 2020 to August 2020) compared with the equivalent period in 2019. Although the total number of patients presenting with gallstone disease was comparable, there was a decrease in patients with cholecystitis and perforation (although it is possibly too early for these to have presented), and there was a small but worrying increase in patients with gallstone pancreatitis. With the recent increase in alert level to 4 and increased government restrictions in an attempt to avoid a second national lockdown, a consistent national approach is required to mitigate these risks.